The Effectiveness of the Use of the Pelindo E-Office Application in the Correspondence Process of PT Pelabuhan Indonesia (Persero) Regional 4 - Fitriani, Rezky; Darwis, Muh; Nasrullah, Muh (Pinisi Journal of Officers Review, 2025)
Effectiveness is an evaluation or measurement of the achievement of a predetermined goal, which is a comparison of the results that have been achieved. The effectiveness of using the E-Office application in the correspondence process fulfils the purpose of its use within a predetermined scope at the company. This study aims to determine the effectiveness of the use of the Pelindo E-Office Application in the Correspondence Process of PT Pelabuhan Indonesia (Persero) Regional 4. This research is qualitative, so the data collection techniques used are observation, interview, and documentation techniques. The number of informants in this study was 7 people. The results of the study show that the management of correspondence using the PEO application has been effective, starting from the ease of accessing the PEO application, features that are by the needs of the users, the security of the data in the PEO application can be guaranteed, the use of more efficient time in completing official manuscripts, the derivatives of letters are clearer and easier, the archiving of letters is clearer, and the application of paperless in PT Pelabuhan Indonesia (Press) Region 4, although the rule is that the provision of mail numbers related to the withdrawal date can only be given by the central TU admin, there is still a need to improve the application related to the provision of mail numbers that are even more effective and human resources who must better master the use of technology in the long term.